متطلبات دعم سوق العمل من أجل تطوير و تنمية المؤسسات الصغيرة و المتوسطة - جديدي, موسى (ENSSEA المدرسة الوطنية العليا للإحصاء و الاقتصاد التطبيقي, 2016)
إن التحولات التي عرفها الاقتصاد الجزائري خلال العقد الأخير من القرن الماضي خلفت العديد من المشاكل و على رأسها اختلال سوق العمل، من تدني للأجور و تفشي للبطالة حيث وصلت إلى مستويات خطيرة، و على غرار العديد من الدول التي اعتمدت في النهوض باقتصادها على قطاع المؤسسات الصغيرة و المتوسطة، و ذلك لما لها من خصائص لا تتوفر في نظيراتها من المؤسسات الكبيرة أو الضخمة و خاصة قدرتها على التأقلم السريع مع المتغيرات العالمية، فلقد أولت الجزائر اهتمام كبير لهذا القطاع و منحته أهمية كبيرة من حيث الدعم. و نهدف من خلال هذا الدراسة إلى تسليط الضوء على سوق العمل في الجزائر، و أثر التغيرات الاقتصادية و الاجتماعية على معدلات البطالة، و كيف تؤثر اختلالات سوق العمل على المؤسسات الصغيرة و المتوسطة و إبراز سعي الدولة الجزائرية للقيام بقطاع المؤسسات الصغيرة و المتوسطة. حيث أن الجزائر و على غرار دول العالم تولي اهتمام خاص لهذا القطاع و ذلك لما له من أهمية بالغة و قدرة على النهوض بالاقتصاد الوطني. لاسيما لما يميز هذا القطاع من قدرة على توفير مناصب العمل و التخفيف من حدث مشكلة البطالة. The Transformation of the Algerian economy during the last decade of the last century have left many problems, on top of which is the disruption of the labor market, from low wages and widespread unemployment, which has reached dangerous levels, and similar to many countries that relied on the advancement of their economy on the small enterprise sector. And because of its characteristics that are not available in its counterparts of large or huge institutions, especially its ability to quickly adapt to global changes, Algeria has paid great attention to this sector and gave it great importance in terms of support. Through this study, we aim to shed light on the labor market in Algeria, the impact of economic and social changes on unemployment rates, and how labor market imbalances affect small and medium enterprises and highlight the Algerian state’s endeavor to establish the sector of small and medium enterprises. Whereas, Algeria, like the countries of the world, pays special attention to this sector, because of its great importance and ability to advance the national economy. Especially for what distinguishes this sector in terms of its ability to provide jobs and alleviate the occurrence of the unemployment problem
أطروحة دكتوراه اقتصاد تخصص اقتصاد و إحصاء تطبيقي
Keywords: سوق العمل، المؤسسات الصغيرة، المؤسسات المتوسطة، البطالة، الاقتصاد الوطني; The labor market, small enterprises, medium enterprises, unemployment, the national economy